El scrapbooking como técnica pedagógica para el mejoramiento del aprendizaje en niños de preescolar con TDAH. - Arroyo, Mishell A. (2022)
The main purpose of this research is to identify and categorize the pedagogical experiences that teachers apply to students with ADHA diagnosis, class mates and the family, based on the three main characteristics of this condition (inattention, hyperactivity and impulsiveness) to determinate the factors that affect the educational process of the students diagnosed with ADHA in their first childhood and linking the familiar and scholar contexts. The methodogical process had a qualitative approach in which were applied semistructured interviews with open questions for each one of the participants, from the results the proposition is to use the Scrapbooking technique to work with ADHA students. Therefore, from the most relevant results obtained, it was posible to determinate the main importance of the Scrapbooking use, within the development of the socio-afective area to keep the student's attention and motivation and as a plastic technique to keep the attention and stimulate the students’ creativity, this technique can use all type decorations like textures, stickers, dry leafs, buttons, ribbons, sequins; it goes from the most soffisticated to the quite simple, getting free the ADHA student's imagination. Acording to the results obtained from the teacher's interviews, it was established that the activities planned for students with ADHA should be developed taking account their capacities and needs; in addition, to adapt teaching methodologies, making them more experimental, artistic and dynamic in such a way that the student's motivation could be kept through the development. In frustrating situations, ADHA students have less emotional self-control to face them, so they tend to go from calm states to exaltation ones, and in sometimes, they turn aggressive with their peers or even with themselves. In conclusion, the need to establish pedagogical guidelines and tools that allow a higher teaching quality process to children with ADHD is evident. Also, implies that it is necessary to do some adjustments and adaptations to the traditional educational models over aspects that these students demand in their pedagogical process. Key words: pedagogical experiences with children with ADHD, ADHD in basic education, behavior disorders, teaching strategies for students with ADHD, Scrapbooking. That is why among the conclusions of this research the need to establish pedagogical guidelines and tools that allow a higher quality teaching process for children diagnosed with ADHD is evidenced. All that has been said so far, also implies that some adjustments and adaptations are made to the traditional educational models on the aspects that these students demand in their pedagogical process and training. Key words: pedagogical experiences with children with ADHD, ADHD in basic education, behavior disorders, teaching strategies aimed at students with ADHD, Scrapbooking. Keywords: pedagogical experiences with ADHD children, ADHD in the basic education, behavior alterations, teaching strategies directed to ADHD students, Scrapbooking.